Meningkatkan Motivasi Belajar Peserta Didik Melalui Penggunaan Teknologi Audio Visual pada Materi Pelajaran Pendidikan Agama Katolik dan Budi Pekerti Pada Siswa Kelas VIII Semester Ganjil Tahun Pelajaran 2024-2025 SMP Negeri 2 Nanga Mahap - Seravina Seravina (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The success of students' learning can be determined by the motivation they have. Students who have high learning motivation tend to excel, on the contrary, low learning motivation will also have low learning achievement. Learning motivation can arise due to internal factors of desire and desire to succeed as well as the drive to learn and achieve goals. The external factors are the existence of awards, a conducive environment, and fun and interesting activities.